Predicting Video Game Addiction Through the Dimensions of Consumer Video Game Engagement: Quantitative and Cross-sectional Study - Amir Zaib Abbasi; Umair Rehman; Zahra Afaq; Mir Abdur Rafeh; Helmut Hlavacs; Mohammed A Mamun; Muhammad Umair Shah (JMIR Publications, 2021)
BackgroundVideo games are expanding exponentially with their increased popularity among users. However, this popularity has also led to an increase in reported video game addiction. There may be consumer engagement-related factors that may influence video game addiction. ObjectiveThis study aims to empirically examine the impact of the dimensions of consumer video game engagement on video game addiction. The dimensions are dedication, absorption, conscious attention, social connection, enthusiasm, and interaction. We utilize the uses and gratifications theory to study the video game engagement dimensions as potential factors through which gamers feel gratified and engaged in video game playing. Additionally, this study incorporates the cultivation theory to investigate how video game engagement factors trigger video game addiction. MethodsA two-step process was applied for data analysis on valid cases of 176 gamers aged 15-25 years: video game addiction was specified and validated as a reflective-formative construct, and hypothesis testing was later performed using the WarpPLS on valid respondents. ResultsThe analysis uncovered 2 dimensions of video game engagement: social connection with P=.08 and interaction with P=.49, which did not significantly contribute to video game addiction. ConclusionsThis study offers unique insights to a myriad of stakeholders, mostly psychologists and psychiatrists, who routinely prescribe behavior modification techniques to treat video game addiction.